DESCRIPTION OF ECONOMIC OUTLOOK AND SOCIAL LIFE IN THE BOOK OF TANOBCHILAR - Abdurahmonov Abdulaziz Xujamurot ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The conflict between the poet’s worldview and aspirations and the environment has created a critical direction in his work. This was reflected more in his comedy. He has created about 30 comic works: "Tanobchilar", "Saylov", "Dar mazammati zamona", "Hajvi khalifa Mingtepa", "Devonamen", "Kosamen", "Hayron edi mud", "Pashshalar", "Shikoyati decoration ”,“ Description oven ”,“ Cart curse ”,“ Clay ”.